Exploring Millennial Consumers’ Behaviour in Social Commerce - Ramnarain, Yavisha; Govender, Krishna K.; Soni, Sanjay (International Review of Management and Marketing, 2024)
This study aims to examine how ratings, forums, communities, reviews, recommendations, and referrals influence consumers who participate in social commerce using Facebook. The target population for this quantitative online study was young adults between the ages of 25 to 34 who are referred to as Millennials and comprise the largest group of users on Facebook. Convenience sampling, namely snowball sampling was used to target the participants. It was ascertained that social commerce constructs are associated with trust which leads to the consumers purchasing decisions. The implication for social commerce is that the information shared over social commerce constructs in cohesive networks is more likely to influence the consumers’ decisions than in less cohesive networks. This, therefore, justifies recommending that businesses should monitor the quality and content of the engagements around their brands on social media since information sharing in social commerce influences the decisions of consumers.